2020
DOI: 10.17816/ov16065
|View full text |Cite
|
Sign up to set email alerts
|

Two-stage or single-stage vitreoretinal surgery with phacoemulsification in patients with advanced proliferative diabetic retinopathy?

Abstract: The literature review compares the combined (vitreoretinal surgery with silicone tamponade and phacoemulsification of incipient cataract with intraocular lens implantation) and two-stage (phacoemulsification with intraocular lens implantation as a second step, simultaneously with the silicon oil removal, after vitreoretinal surgery) surgical treatment of patients with advanced proliferative diabetic retinopathy and complicated incipient cataract. Modern concepts of treatment tactics of this disease, its effica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…However, the optimal timing and approach for combined surgery remain controversial. A comparative analysis of two-stage or simultaneous vitreoretinal surgery results with phacoemulsification in patients with advanced proliferative diabetic retinopathy and complicated incipient cataract showed that both approaches could be practical [91,92]. The choice of approach may depend on the severity of the retinopathy and the degree of cataract.…”
Section: Eyes With Sequential/simultaneous Vitreoretinal Surgerymentioning
confidence: 99%
“…However, the optimal timing and approach for combined surgery remain controversial. A comparative analysis of two-stage or simultaneous vitreoretinal surgery results with phacoemulsification in patients with advanced proliferative diabetic retinopathy and complicated incipient cataract showed that both approaches could be practical [91,92]. The choice of approach may depend on the severity of the retinopathy and the degree of cataract.…”
Section: Eyes With Sequential/simultaneous Vitreoretinal Surgerymentioning
confidence: 99%